Inflammatory markers in pediatric stroke: An attempt to better understanding the pathophysiology. (March 2016) - Buerki, Sarah E.; Grandgirard, Denis; Datta, Alexandre N.; Hackenberg, Annette; Martin, Florence; Schmitt-Mechelke, Thomas; Leib, Stephen L.; Steinlin, Maja; ,
Abstract: Background: The mechanisms of childhood and perinatal arterial ischemic stroke (AIS) are poorly understood. Multiple risk factors include cerebral arteriopathy, congenital cardiac disease, infection, sickle cell disease, and maternal–fetal conditions in neonates. For infections and parainfectious conditions being the most important a possible inflammatory pathophysiology has long been suspected. This pilot study aims to detect, whether there are any abnormalities of inflammatory markers associated with childhood and neonatal stroke. Methods: The concentration of 23 different metalloproteinases (MMPs), tissue inhibitors of MMPs (TIMPs), endothelial factors, vascular cell adhesion proteins, and cytokines in plasma were measured in 12 children with AIS, 7 healthy age matched controls and 6 full term neonates with perinatal AIS. Results: At the time of the acute event children with AIS had significantly elevated levels of MMP-9, TIMP4, IL-6, IL-8 and CRP compared to controls ( p < 0.05). Except for lower IL-6 and CRP levels the pattern of children with a history of varizella-zoster virus (VZV) and other viral infections did not differ to the non-infectious group. Median levels of MMP-1, MMP-2, TIMP-1, TIMP-2, sE-selectin, sICAM-1, sVCAM-1, IL-8, IL-10, TNF-alpha, VEGF, Fetuin A were found to be higher in the neonatal group when compared with older children. Conclusion: This pilot study supports the assumption of an inflammatory process and up-regulation of metalloproteinases and their inhibitors, and altered pattern of circulating pro-inflammatory cytokines, CRP and vWF levels in pediatric and neonatal AIS. It highlights the feasibility but also difficulties for similar larger future studies that should aim to clarify childhood stroke etiopathogenesis and consecutive further therapeutic options. Highlights: A possible inflammatory pathophysiology has been suspected in pediatric arterial ischemic stroke. This pilot study supports the assumption of an inflammatory process in pediatric and neonatal arterial ischemic stroke. Children and neonates with arterial ischemic stroke showed a significant up-regulation of metalloproteinases. Children and neonates had a different inflammatory pattern of circulating pro-inflammatory cytokines in plasma.